Flow-injection spectrophotometric determination of novalgin in phrmaceuticals using micellar medium - Weinert, Patricia Los [UNESP]; Fernandes, João Roberto [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Japan Soc Analytical Chemistry, 2007)
A sensitive flow-injection (FI) procedure with spectrophotometric detection in a micellar medium is proposed for the determination of novalgin. The method is based on the instantaneous formation of a red-orange product (lambda(max) = 510 nm) after the reaction between novalgin and p-dimethylaminocinnamaldehyde (p-DAC) in a dilute acid medium. The sensitivity of this reaction was increased by a factor of 5.6 in the presence of sodium dodecyl sulfate (SDS). Experimental design methodologies were used to optimize the chemical and FI variables. The calibration curve was linear in the range of 1.45 x 10(-6) to 2.90 x 10(-5) mol L-1 with an excellent correlation coefficient (r = 0.9999). The detection limit was 1.31 x 10(-7) mol L-1 (n = 20, RSD = 2.0%). No interferences were observed from the common excipients. The results obtained by the proposed method were favorably compared with those given by the iodometric reference method at 95% confidence level.